Similar but Different: Comparative Seed Policy Implementation for Food Security in Indonesia and Malaysia - Dini Eka Prasasti (Goodwood Publishing, 2026)
Purpose: This study aims to compare the implementation of high-quality seed and seedling management policies in Indonesia and Malaysia and to understand their role in strengthening national food security. Research Methodology: This study employs a qualitative comparative approach focusing on Indonesia and Malaysia as ASEAN countries with different agricultural governance systems. Data were collected through document analysis of national regulations, policy reports, agricultural plans, and official publications related to seed and seedling management. The analysis applies a policy implementation framework to examine institutional arrangements, distribution systems, and stakeholder involvement, relying solely on secondary data. Results: The findings show clear differences in policy implementation between the two countries. Malaysia has developed an integrated seed management system supported by strong institutions, digital distribution mechanisms, and continuous research and development. This system encourages compliance and effective user behavior among farmers. Indonesia, however, remains at an early implementation stage, facing challenges such as fragmented institutions, limited coordination, and inefficient seed distribution systems. These conditions reduce policy effectiveness and slow progress toward food security goals. Conclusions: The study concludes that institutional coherence, digital governance, and strong research support are critical factors in successful seed policy implementation. Limitations: This study is limited to document-based analysis and does not include field observations or farmer interviews. Contributions: This study contributes to agricultural policy studies, food security research, and comparative public policy by providing insights for policymakers, researchers, and regional institutions in ASEAN.